Assessment of the Effects of the Synbiotic Combination of Bifidobacterium longum subsp. infantis CECT 7210 and Oligofructose-Enriched Inulin Against Digestive Bacterial Infections in a Piglet Model - Rodríguez-Sorrento, Agustina; Castillejos, Lorena; López-Colom, Paola; Cifuentes-Orjuela, Gloria; Moreno-Muñoz, José A.; Martín-Orúe, Susana M. (Frontiers in Microbiology, 2022)
The use of bifidobacteria as probiotics has proven to be beneficial in gastroenteric infections. Furthermore, prebiotics such as inulin can enhance the survival and growth of these bacteria. Two trials were performed to evaluate the effects of the administration of Bifidobacterium longum subsp. infantis CECT 7210 and oligofructose-enriched inulin against Salmonella enterica serovar Typhimurium or enterotoxigenic Escherichia coli (ETEC) F4. A total of 72 (Salmonella trial) and 96 (ETEC F4 trial) weaned piglets were used in a 2x2 design (with or without synbiotic, inoculated or not with the pathogen). After adaptation, animals were orally inoculated. Performance and clinical signs were evaluated. On days 4 and 8 (Salmonella trial) and 3 and 7 (ETEC F4 trial) post-inoculation (PI), one animal per pen was euthanized. Blood, digestive content and tissue samples were collected and microbiological counts, fermentation products, serum inflammatory markers and ileum histomorphometry analysis were performed. Both challenges had an impact on faecal consistency (P < 0.001), including the faecal shedding of Salmonella and increased numbers of enterobacteria and coliforms. The synbiotic administration did not have any effect on pathogen loads, but induced changes in the fermentation profile, such as increased valeric acid in both trials as well as decreased acetic acid, except for in Salmonella-challenged animals. The effect on propionate varied among trials, increasing in challenged synbiotic-treated pigs and decreasing in non-challenged ones in the Salmonella trial (P interaction = 0.013), while the opposed occurred in the ETEC F4 trial (P interaction = 0.013). The administration of the synbiotic increased intraepithelial lymphocytes (IEL) (P = 0.039) on day 8 PI in the Salmonella trial and a similar trend occurred in non-challenged pigs in the ETEC F4 trial (P interaction = 0.086). The results did not provide evidence of reduced pathogen load with the synbiotic, although a modulation in fermentative activity could be identified depending on the challenge. Consistent increases were found in IEL, suggesting that this synbiotic combination has some immunomodulatory properties.